Chondroitin sulfate B and heparin mediate adhesion of Penicillium marneffei conidia to host extracellular matrices - Yuttana Srinoulprasert (2018)
Penicilliosis is a disseminated infection in immunocompromised individuals caused by the dimorphic fungus, Penicillium marneffei. Very little is known about its route of infection, however, it is thought that initial infection occurs through inhalation of conidia. We investigated the role played by various extracellular matrix glycosaminoglycans (GAGs) in the initial adherence of P. marneffei conidia using a direct adhesion assay. GAGs were further used to block the binding of fungal spores to human lung epithelial cells and highly sulfated GAGs were tested for their inhibitory effects owing to their degree of sulfation. Our results demonstrated high levels of conidial adhesion to chondroitin sulfate B, heparin and highly sulfated chitosan (CP-3). No direct adherence was observed to immobilized chondroitin sulfate (CS) A, CSC, CSD and hyaluronic acid, as well as chitosans with low sulfate content. The results suggested that P. marneffei conidia bind to iduronic acid (IdoA) of the polysaccharide chains. Involvement of negatively charged sulfate groups in adhesion was also indicated. Furthermore, significant inhibition of conidial adherence to A549 cells was observed in the presence of CSB, heparan sulfate (HS), heparin and CP-3. It was further demonstrated that GAGs can affect the adhesion of conidia to fibronectin and laminin, glycoproteins that have previously been implicated as adhesive receptors for fungal conidia. CSB and HS could partially inhibit the adhesion of fungal conidia to laminin and fibronectin implying that conidia can weakly interact with the IdoA GAG-binding domain(s) of these molecules. The data indicated that, in addition to fibronectin and laminin, IdoA-containing GAGs may play an important role in fungal adherence to the surface of human lung epithelium. © 2005 Elsevier Ltd. All rights reserved.